Isometric training and long‐term adaptations: Effects of muscle length, intensity, and intent: A systematic review. (13th January 2019) - Oranchuk, Dustin J.; Storey, Adam G.; Nelson, André R.; Cronin, John B.
Abstract : Isometric training is used in the rehabilitation and physical preparation of athletes, special populations, and the general public. However, little consensus exists regarding training guidelines for a variety of desired outcomes. Understanding the adaptive response to specific loading parameters would be of benefit to practitioners. The objective of this systematic review, therefore, was to detail the medium‐ to long‐term adaptations of different types of isometric training on morphological, neurological, and performance variables. Exploration of the relevant subject matter was performed through MEDLINE, PubMed, SPORTDiscus, and CINAHL databases. English, full‐text, peer‐reviewed journal articles and unpublished doctoral dissertations investigating medium‐ to long‐term (≥3 weeks) adaptations to isometric training in humans were identified. These studies were evaluated further for methodological quality. Twenty‐six research outputs were reviewed. Isometric training at longer muscle lengths (0.86%‐1.69%/week, ES = 0.03‐0.09/week) produced greater muscular hypertrophy when compared to equal volumes of shorter muscle length training (0.08%‐0.83%/week, ES = −0.003 to 0.07/week). Ballistic intent resulted in greater neuromuscular activation (1.04%‐10.5%/week, ES = 0.02‐0.31/week vs 1.64%‐5.53%/week, ES = 0.03‐0.20/week) and rapid force production (1.2%‐13.4%/week, ES = 0.05‐0.61/week vs 1.01%‐8.13%/week, ES = 0.06‐0.22/week). Substantial improvements in muscular hypertrophy and maximal force production were reported regardless of training intensity. High‐intensity (≥70%) contractions are required for improving tendon structure and function. Additionally, long muscle length training results in greater transference to dynamic performance. Despite relatively few studies meeting the inclusion criteria, this review provides practitioners with insight into which isometric training variables (eg, joint angle, intensity, intent) to manipulate to achieve desired morphological and neuromuscular adaptations.